Colorectal Cancer Mortality Across the American Continent: Temporal Trends - Lopes, Lucas Casagrande Passoni (Journal of Coloproctology, 2025)
Colorectal cancer (CRC) is a major global health concern and a leading cause of cancer-related mortality. Understanding temporal trends in CRC mortality is crucial for guiding public health policies and resource allocation.To evaluate the temporal trends of CRC mortality rates across the American continent.This retrospective, population-based study used data from the Pan American Health Organization for its development. Age-adjusted mortality rates per 100,000 individuals were collected for the period 2000–2019 and stratified by country and sex. Joinpoint regression analysis was conducted to estimate the annual percentage change (APC) and assess temporal trends.CRC mortality trends varied across regions and sexes. In South and Central America, mortality rates increased, particularly in the early 2000s, whereas North America experienced a general decline. Gender-specific trends showed significant increases in South and Central American women, while men exhibited rising trends except in North America, where rates steadily declined.The study identified distinct trends in CRC mortality across the Americas, with increasing rates in some countries and declines in others. Socioeconomic factors, healthcare access, and sex-based differences appear to contribute to these variations. These findings underscore the need for targeted public health strategies to reduce colorectal cancer burden and address disparities in early detection and treatment.
Keywords: America; mortality; colorectal cancer; sex